Kasata klasztoru benedyktynów w Lubiniu - Pukianiec, Mikołaj (Ecclesia. Studia z Dziejów Wielkopolski, 2010)
Following the second partition of Poland, the Benedictine Monastery in Lubiń found itself within part annexed by Prussia. Government guaranty of immunity of Church property turned out to be a farce as early as 1795, while subsequent rulings of Friedrich Wilhelm II led to the ruin of one of the most famous centres of monastic life in the former Republic of Poland. Monastery lands were nationalized, a ban was introduced on the admission of candidates to the novitiate and after a time requisition of the monks' movable property was enforced. The process of suppression was brought to a completion when buildings formerly belonging to the monastery were torn down. Only one apartment was spared where two clergymen were allowed to live. The church of the former Lubiń parish of St. Leonard was handed over to the Evangelical community. Almost half a century passed between the death of the last of the 19th century monks in Lubiń and the return of the Benedictines in 1932. The memory of those events lives in the call that accompanies the Bene- dictine order - ,,Succisa virescit" - the truncated  regenerates.